SACCADE AND PURSUIT ON AN ACTIVE HEAD EYE PLATFORM - Bradshaw, K; Mclauchlan, P; Reid, I; Murray, D (1994)
We describe the implementation of, and results from a realtime active surveillance vision system which detects moving objects in an everyday environment, directs the gaze of a head/eye platform towards the objects and subsequently pursues them smoothly. Target detection and pursuit are performed purely on the basis of image motion, and can continue over extended periods. Two independent parallel processes derive (i) coarse resolution motion over the entire image to direct saccadic shifts in attention over a wide field of view, and (ii) fine resolution motion in a small central region of the image used to perform smooth-pursuit. A gaze controller which selects results from the two visual processes and controls the movement of the head platform is implemented as a finite state machine. © 1994.